International law and arms control: Soviet Union and Russia’s stance on nuclear test ban treaties - Dalaqua, Renata Hessmann (2017)
The long-lasting struggle against nuclear tests can be examined through different perspectives. In this paper, the focus will be on the part played by the USSR and Russia in the international efforts aimed at establishing legal instruments to outlaw nuclear explosions in space, underground, under water and in the atmosphere.